A cross-sectional study on factors contributing to nosocomial infections in medical wards in Mengo Hospital. - Nalwoga, Patricia; Nyiramahoro , Salome; Oromcan , Benjamin Wathum (Student's Journal of Health Research Africa, 2025)
Introduction This study aimed to determine the factors contributing to Nosocomial infections (NIs), common isolates, and their susceptibility patterns associated with NIs in medical wards in Mengo Hospital. Method A cross-sectional study involving 84 patients attending medical wards in Mengo Hospital from August 2024 to November 2024 was carried out. Upon consenting, study subjects were enrolled in the study. Samples were collected from the study subjects who presented with NIs and taken to the laboratory for culture and susceptibility testing. The results obtained were recorded and analyzed using statistical packages SPSS version 25 and presented as tables and figures with clear narratives under them. Results Out of the 84 patients recruited and studied, the general prevalence of NIs was high at 52.4%. Factors associated with NIs among the study participants were catheterization (70.5%), over a month hospitalization of patients (65.9%), and prior intake of antibiotics (56.8%). Commonly isolated microorganisms associated with NIs were Pseudomonas aeruginosa 11.9% (10/84), Candida albicans 10.7% (9/84), and Klebsiella pneumoniae 7.1% (6/84). Resistance profile ranged from 14.3% to 84.6%. Most of the isolates showed resistance against Ceftriaxone (84.6%), Ceftazidime (68.4%), and Nitrofurantoin (64.7%). Meanwhile, better sensitivity patterns were recorded against Amphotericin B (85.7%), Imipenem (84.6%), and Tetracycline (80%). Conclusions Nosocomial infections among patients at medical wards in Mengo Hospital are high (52.4%) and present a significant public health problem. Recommendations Given the high prevalence of NIs and antimicrobial resistance (AR), there is a need for public awareness, strict hygiene practices in medical wards, and the implementation of antibiotic stewardship programs. Further research is essential to understand the epidemiology and resistance patterns of NIs to inform policy and guide effective interventions.